Pengaruh Capital Adequacy Ratio, Non-Performing Financing, Financing to Deposit Ratio dan Rasio Biaya Operasional dengan Pendapatan Operasional terhadap Return On Asset sebagai Indikator Profitabilitas - Samuel Martono; Nurul Rahmawati (Universitas Pendidikan Ganesha, 2020)
This study aims to examine the effect given by Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Financing to Deposit Ratio (FDR) and Operating Income and Operating Expense Ratio to Return on Asset as Profitability Indicator. Data population are Indonesian Sharia Banks listed in Indonesia Stock Exchange during period 2013-2017, and obtained 11 sharia banks as the total sample are 55 samples by using purposive sampling method. Multiple regression analysis models is used in this study. The results are as follows: there are no effect given by CAR, NPF, FDR to ROA but there is partial effect given by Operating Income and Operating Expense Ratio.